Bowling for Fascism: Social Capital and the Rise of the Nazi Party - Satyanath, Shanker; Voigtländer, Nico; Voth, Hans-Joachim (Journal of Political Economy, 2017)
Using newly collected data on association density in 229 towns and cities in interwar Germany, we show that denser social networks were associated with faster entry into the Nazi Party. The effect is large: one standard deviation higher association density is associated with at least 15 percent faster Nazi Party entry. Party membership, in turn, predicts electoral success. Social networks thus aided the rise of the Nazis that destroyed Germany’s first democracy. The effects of social capital depended on the political context: in federal states with more stable governments, higher association density was not correlated with faster Nazi Party entry.